2021
DOI: 10.1039/d0fo02855j
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in mental health and depression: role of pre/pro/synbiotics in their modulation

Abstract: Microbiome residing in the human gut perform a wide range of biological functions. Recently, it has been elucidated that change in the dietary habits is associated with alteration in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 269 publications
1
14
0
Order By: Relevance
“…Free fatty acid receptor 2 is expressed on enteroendocrine cells and is known to bind SCFAs [11,57]. Importantly, free fatty acid receptor activation stimulates the release of glucagon-like peptide-1 and peptide YY into the blood stream, which regulate post-prandial release of insulin and satiety, respectively [84]. Chronic stress is also known to decrease GLP-1 levels in the paraventricular nucleus of the hypothalamus, dysregulating eating behaviour [85].…”
Section: Intestinal Barrier Integrity Pathwaysmentioning
confidence: 99%
“…Free fatty acid receptor 2 is expressed on enteroendocrine cells and is known to bind SCFAs [11,57]. Importantly, free fatty acid receptor activation stimulates the release of glucagon-like peptide-1 and peptide YY into the blood stream, which regulate post-prandial release of insulin and satiety, respectively [84]. Chronic stress is also known to decrease GLP-1 levels in the paraventricular nucleus of the hypothalamus, dysregulating eating behaviour [85].…”
Section: Intestinal Barrier Integrity Pathwaysmentioning
confidence: 99%
“…In terms of how to control the intestinal microbiota in our daily lives, moderate exercise is suggested to have beneficial effects on health, such as reducing inflammation and intestinal permeability and improving the body composition [ 8 ]. In addition, mental health initiatives such as stress reduction and improvement of the oral environment are also effective in preserving the intestinal environment [ 9 , 10 ]. As the concept of preventive medicine grows in importance, this assertion will gain more credibility.…”
Section: Introductionmentioning
confidence: 99%
“…The elevation in the aggressive peck negatively correlates with the nonaggressive pecks, e.g., for playing [ 55 ]. It may underline the previous findings that the early life adverse impacts can be buffered and masked by the favorable experience at a later age, such as the environmental enrichment or social support from other birds [ 56 ].…”
Section: Discussionmentioning
confidence: 74%
“…Imbalance of gut microbiota is associated with neuroinflammation and psychiatric disorders in humans and various experimental animals [ 19 , 20 ]. Modulation of gut microbiota using prebiotics, probiotics, and synbiotics to regulate the MGB axis has been used as an alternative to antidepressant therapy in humans [ 56 ]. In the current study, the reprogrammed MGB axis was found along with the decreased BW and aggression.…”
Section: Discussionmentioning
confidence: 99%